An Analysis & Sector Wise Comparison of Corporate Social Responsibility by Companies in India - Singh, Vikrant Vikram; Pandey, Manoj; Vashisht, Anil (International Research Journal of Management, IT & Social Sciences, 2016)
The study looks at the Corporate Social Responsibility (CSR) of Indian firms from various sectors and its impact on the performance and market execution of firms. The study looks at the CSR contribution of various firms and its impact on profit after tax over a three year period from 2013 to 2015. The study utilizes substance investigation to study CSR revelation and characterizes and rates these exercises utilizing things from a set up scale took after by development of class shrewd CSR records. This study also analyzes the CSR activities of various sectors in India by covering wide range of activities done by various leading companies of these sectors. The study finds that CSR reporting may have any critical effect on market performance and market execution of the firm in the fleeting yet environment situated CSR exposure may be adversely identified with the business sector execution of the firm. The concentrate additionally finds that organizations concentrate intensely on representative and client arranged CSR and the methods of CSR ventures are more contributory as opposed to participative in nature. This study also finds that various leading sectors in India are very focused and dedicated in terms of CSR activities and there is a kind of competitive environment among the companies for participating in CSR activities, which is actually a very good sign.Â